Saving the old apple tree : a book about caring for the environment. (Asia : Time Life Asia, 1997)
To make way for a new railway, much-loved old apple tree in a quite country village is threatened with being cut down. As the adults of the village take up their saws and axes, it is up to the children to remind them of the importance of nature and environment.
w/ casette tape
Keywords: Values; Environment - Fiction